An integrated cynefin-vee framework for complex product system (CoPS) projects - Lim, Ruishen (2016)
Project management techniques have evolved over time with various frameworks attempting to capture and guide the management of the temporary endeavours known as projects, which are undertaken to create unique products, services or results. The systems demanded by society and subsequently, the projects, have grown exponentially in size and complexity over time. Complex product systems (CoPS) have come to be identified as complex, high value products, systems and constructs, requiring engineering-intensive processes. In this dissertation I argue that traditional project management frameworks suffer from being unable to capture the complexities in CoPS and can lead to problems and frustration if used without the appreciation of such behaviours. From the Dave Snowden's Cynefin framework which identifies different domains of complexity, as well as the "Vee" model used in most project management today, I create an integrated model meant to help visualization of where different levels complexity occurs in CoPS project lifecycles. I then perform a case study involving four CoPS projects, each forming systems in a larger CoPS. I demonstrate that results from the case study indicate the accuracy of the framework, and argue the usefulness of the framework through its acknowledgement of complexity in a CoPS project lifecycle. The work in this dissertation aims to benefit education in project management and systems engineering through better visualization of the project lifecycle. In particular, it will aid lesser experienced project managers and systems engineers in understanding the flow of complexity within these projects.